A Case of Onychomycosis with Nail Lichen Planus: The Importance of Supportive Examinations in Establishing a Diagnosis - Ariani, Tutty; Farhanah, Nindya; Gustia, Rina (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Onychomycosis and Nail Lichen Planus (NLP) are two conditions that cause nail damage and may sometimes present with overlapping clinical features, leading to difficulties in achieving an accurate diagnosis. Several ancillary examinations should be considered to avoid misdiagnosis of nail disorders. Case: A 64-year-old female patient presented to the Dermatology, Venereology, and Aesthetic Clinic at Dr. M. Djamil General Hospital Padang with complaints of progressive nail thickening and whitening affecting almost all nails, occasionally accompanied by itching, for the past 6 months. The patient had previously been diagnosed with onychomycosis and had regularly taken fluconazole 150 mg weekly for 6 months, but without improvement. Physical examination was within normal limits. Dermatological and onychoscopic examination revealed subungual hyperkeratosis, longitudinal ridging, onychotrophy, onychoschizia, trachyonychia, onycholysis, yellowish discoloration, melanonychia, and leukonychia, with an OSI score indicating severe involvement and a NALSI score of 100/120. KOH examination demonstrated the presence of hyphae, fungal culture revealed Aspergillus niger, PAS staining confirmed fungal elements, while biopsy results were consistent with NLP. The patient was diagnosed with onychomycosis with concomitant NLP and was treated with pulse itraconazole at a dose of 400 mg/day for one week each month for 2–3 months. Upon completion, treatment for NLP was initiated. Discussion: In this case, the absence of comprehensive ancillary examinations particularly biopsy, initially led to a diagnosis limited only to onychomycosis, without recognition of the coexisting NLP. This highlights the importance of thorough investigations to ensure an accurate and precise diagnosis.